CIMAT: a knowledge-based system for developing criteria & indicators for sustainable forest management - Haggith, M.; Prabhu, Ravi; Purnomo, H.; Rizal, A.; Taylor, J.; Yasmi, Yurdi; Sukadri, D. (1999)
The Center for International Forestry Research (CIFOR) has carried out research to develop Criteria and Indicators for sustainable forest management (C&I) in eight countries since 1994. In the CIFOR framework C&I are organised hierarchically as principles, criteria, indicators, and verifiers. Based on an analysis and synthesis of the C&I research a set of C&I has been identified that can form the starting point for developing localised sets of criteria and indicators. This set is called the "Generic Template". A Knowledge based system called CIMAT (Criteria and Indicators Modification and Adapation Tool) has now been developed to support the process of developing locally adapted C&I using the Generic Template are represented as items that can be modified by the user. The modification can only take place when users explain their reason for the change. All the reasons in the system can be made dependent upon one to another, they can be revised during modification, and they can be counter-argued by other users. The need to represent and maintain these reasons and their interdependencies is resolved through the use of a reason maintenance system (RMS). Another meta-level component of CIMAT is its ability to compare and analyze multiple knowledge bases.